Al-Haya’ Dalam Perspektif Psikologi Islam: Kajian Konsep Dan Empiris - Cintami Farmawati (Jurnal Studia Insania, 2020)
The phenomenon of the character of shame (al-haya’) is now very factual. The culture of shame slowly began to disappear with the global process of assimilation, the shameless character of the eastern culture began to adopt the character of western culture which resulted in the loss of shame. The impact of the loss of shame in a person is that all of his behavior is difficult to control and will commit a variety of dishonorable acts such as corruption, cheating, cheating, displaying the genitals with sexy and mini clothes, adultery, drunkenness, piracy, sexual harassment, murder and others. While Islam strongly emphasizes the character of shame as a good moral. This study aims to see how the concept of al-haya 'in the perspective of Islamic psychology through conceptual and empirical studies. The study in this study was carried out with two events namely, the first with a literature review and the second an empirical study. Literature studies include the study of the verses of the Koran, Hadith and opinions of Islamic leaders who discuss al-haya '. The second study is through an empirical way by conducting interviews with 2 Ustadz and 3 students majoring in Sufism and Psychotherapy who have successfully applied al-haya 'in their daily lives. This research is included in qualitative research with a grounded theory design. The results showed that al-haya 'which is interpreted by the research subjects is almost the same as what is contained in Islamic studies. Al-haya ’is a shame that is driven by respect and aversion to something that is seen as insulting or violating the principles of sharia. People who have the character of al-haya 'are those who want to do something deed but then undo their intentions because there are bad consequences that can reduce the dignity of himself in the eyes of respected people